"A Part of Our Family"? Effects of Psychiatric Service Dogs on Quality of Life and Relationship Functioning in Military-Connected Couples. (6th October 2020) - McCall, Christine E.; Rodriguez, Kerri E.; MacDermid Wadsworth, Shelley M.; Meis, Laura A.; O'Haire, Marguerite E.
Abstract: Posttraumatic stress disorder (PTSD) can have corrosive impacts on family relationships and individual functioning. Emerging evidence has shown that psychiatric service dogs may be an effective complementary treatment for military veterans with PTSD, benefiting veterans' mental and social health. However, few studies have examined the effects of psychiatric service dogs on the family members of veterans, specifically their partners. Mixed-methods data from 60 veteran-partner dyads examined individual and relationship functioning among partners of veterans paired with a service dog (service dog group; n = 37) and those awaiting placement (waitlist group; n = 23). While there were no statistically significant differences across groups, the effect sizes for group differences suggested that partners in the service dog group (relative to those on the waitlist) may experience higher levels of resilience and companionship, and lower levels of anger, social isolation, and work impairment. A topical survey of partner qualitative data within the service dog group indicated that service dogs provided more benefits than challenges. Partners reported improvements in veteran functioning, family relationships, and partners' quality of life. Results, although preliminary, suggest that psychiatric service dogs may provide modest positive experiences for some veteran family systems.